2023
DOI: 10.1002/aenm.202203689
|View full text |Cite
|
Sign up to set email alerts
|

Stackable Direct Current Triboelectric‐Electromagnetic Hybrid Nanogenerator for Self‐Powered Air Purification and Quality Monitoring

Abstract: Triboelectric nanogenerators (TENGs) and electromagnetic generators (EMGs) show their strengths in harvesting mechanical energy from ambient environment, while the output characteristics of the hybrid generators are not optimally utilized. Here, a stackable triboelectric‐electromagnetic hybrid nanogenerator is designed to construct a self‐powered environmental governance system that fully harnesses the high‐voltage output of TENG and high‐current output of EMG, respectively. Based on the corona discharge, a cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…As Figure 18E shows, Chen et al developed a statable hybrid NG that utilized the flexible contact between ethylene-propylene fluoride and silver fiber cloth generated through corona discharge to realize cylindrical direct-current TENG (DTENG) for a self-powered environmental governance system. 308 The results showed a discharge rate of −7.166 μC s −1 and a voltage of −21.61 kV at 1300 rpm for the two stacked DTENGs. In addition, the EMG component could achieve a rectified average power of 2.51 W. Finally, the airflow enabled the hybrid NG to release negative ions for powering the air quality detector.…”
Section: Hybrid Ngmentioning
confidence: 91%
See 1 more Smart Citation
“…As Figure 18E shows, Chen et al developed a statable hybrid NG that utilized the flexible contact between ethylene-propylene fluoride and silver fiber cloth generated through corona discharge to realize cylindrical direct-current TENG (DTENG) for a self-powered environmental governance system. 308 The results showed a discharge rate of −7.166 μC s −1 and a voltage of −21.61 kV at 1300 rpm for the two stacked DTENGs. In addition, the EMG component could achieve a rectified average power of 2.51 W. Finally, the airflow enabled the hybrid NG to release negative ions for powering the air quality detector.…”
Section: Hybrid Ngmentioning
confidence: 91%
“…This study demonstrated a new design and method to improve the output performance of TENGs, providing a good prospect for constructing a self-powered water sensing system driven by low-frequency water waves. As Figure E shows, Chen et al developed a statable hybrid NG that utilized the flexible contact between ethylene-propylene fluoride and silver fiber cloth generated through corona discharge to realize cylindrical direct-current TENG (DTENG) for a self-powered environmental governance system . The results showed a discharge rate of −7.166 μC s –1 and a voltage of −21.61 kV at 1300 rpm for the two stacked DTENGs.…”
Section: Hybrid Ngmentioning
confidence: 99%
“…On the other hand, a triboelectric nanogenerator (TENG) is a compelling energy harvesting technology, 11,12 which exhibits crucial potential for mechanical energy harvesting and active sensing based on the coupling of contact electrification and electrostatic induction. 13,14 Due to diverse electricity generation mechanisms and energy input characteristics, a TENG can be integrated with many other technologies, such as an electromagnetic generator (EMG), 15 a piezoelectric nanogenerator (PENG), 16 a solar cell (SC), 17 and a thermoelectric generator (ThEG), 18,19 to develop a multi-functional hybrid generator. There have been many efforts devoted to combining a TENG with a ThEG for achieving efficient harvesting of multiple energies.…”
Section: Introductionmentioning
confidence: 99%
“…[23] The TENG for harvesting wind energy mainly includes windinduced vibration mode [24][25] and rotation mode. [26][27][28][29] For the rotating TENGs, the output performance is proportional to the driving torque of the energy harvesting devices. [30] Presently, the rotating TENGs mainly adopt wind cups [31][32][33][34] or windmills [35] to harvest wind energy.…”
Section: Introductionmentioning
confidence: 99%